Impact of Road Traffic Pollution on Pre-eclampsia and Pregnancy-induced Hypertensive Disorders - Pedersen, Marie (Epidemiology, 2017)
BACKGROUND: Road traffic is a major source of air pollution and noise. Both exposures have been associated with hypertension in adults, but pregnant women have been less studied. METHODS: We examined single and joint effects of ambient air pollution and road traffic noise on pre-eclampsia and pregnancy-induced hypertensive disorders among 72,745 singleton pregnancies (1997–2002) from the Danish National Birth Cohort with complete covariate data and residential address history from conception until live born birth. Nitrogen dioxide (NO(2)) and noise from road traffic (L(den)) were modeled at all addresses. Outcome and covariate data were derived from registries, hospital records, and questionnaires. RESULTS: A 10-µg/m(3) increase in NO(2) exposure during first trimester was associated with increased risk of pre-eclampsia (n = 1,880, adjusted odds ratio = 1.07 [95% confidence interval = 1.01, 1.14]) and pregnancy-induced hypertensive disorders (n = 2,430, adjusted odds ratio = 1.07 [1.01, 1.13]). A 10 dB higher road traffic noise was also associated with increased risk of pre-eclampsia (1.10 [1.02, 1.18]) and pregnancy-induced hypertensive disorders (1.08 [1.02, 1.15]). For both exposures, the associations were strongest for mild pre-eclampsia (n = 1,393) and early-onset pre-eclampsia (n = 671), whereas higher risk for severe pre-eclampsia (n = 487) was not evident. In mutually adjusted models, estimates for both exposures decreased and only the association between NO(2) and mild pre-eclampsia remained. CONCLUSIONS: Road traffic may increase the risk of pre-eclampsia and hypertensive disorders in pregnancy through exposure to both ambient air pollution and noise, although associations with the two exposures were generally not found to be independent of one another. See video abstract, http://links.lww.com/EDE/B112.